Human Resource Development Strategy at the Makassar Immigration Detention Center - Hasniaty, Hasniaty; Rafiah, Rafiah; Insan, A. Nur (Jurnal Ilmu Manajemen Profitability, 2025)
This study aims to examine the human resource development strategies implemented at the Makassar Immigration Detention Center (Rudenim) and to formulate recommendations for improving the effectiveness of refugee services. Employing a qualitative approach with a descriptive method, the research involved key informants, including institutional leaders, administrative staff, the Head of the Personnel Affairs Division, and other relevant stakeholders engaged in refugee management at Rudenim Makassar. The findings reveal that Rudenim Makassar possesses strengths such as experienced personnel and well-established immigration policies. However, challenges remain, including heavy workloads, limited administrative technology, and psychological pressures faced by officers in handling refugees. The SWOT analysis highlights the need to address these weaknesses and threats through strategic initiatives. Recommended strategies include strengthening technical and soft skills training, implementing performance-based evaluation systems, adopting technology-driven HR management practices, and establishing stronger collaboration with international organizations such as UNHCR and IOM. These recommendations underscore the importance of sustainable and innovative policies to enhance employee competencies, thereby ensuring that refugee services at Rudenim Makassar are more professional, responsive, and aligned with global humanitarian dynamics.